El acontecimiento de la verdad en la fenomenología ontológica de Jean-Paul Sartre - Cotrina Cosar, Juan Pablo (2019)
This article aims to shed light on the idea of truth in Jean-Paul Sartre’s ontological phenomenology from his posthumous book, Truth and Existence (1989). For this, we will divide our work into four parts: the first will approach the idea of truth as a revelation of Being to human reality; the second will analyze how a denial of truth is possible from the possibilities of ignorance and error; the third will focus on explaining how the truth unveiled by a human reality opens towards universalization; and the fourth will show that all truth, by the fact of being intersubjective, is part of the process of historicalization of human reality.